2018
DOI: 10.2175/106143018x15289915807164
|View full text |Cite
|
Sign up to set email alerts
|

Pulp and Paper Mill Effluent Management

Abstract: This is a review of literature published in 2017 related to the prevention of water pollution by or recovery of beneficial materials from wastewater produced in the pulp and paper industry. This review includes the following main sections: cleaner production, biological treatment, and physico-chemical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To date, the biological and physicochemical processes were applied for the treatment of wood and paper wastewater (Azimi et al, 2019;Elnakar & Buchanan, 2018Gholami et al, 2016Gholami et al, , 2017Kamali & Khodaparast, 2015;Khan et al, 2013). In biological methods, microorganisms are used as a solitary treatment or in the combination with other physical methods and/or chemical technologies (Singhal & Thakur, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the biological and physicochemical processes were applied for the treatment of wood and paper wastewater (Azimi et al, 2019;Elnakar & Buchanan, 2018Gholami et al, 2016Gholami et al, , 2017Kamali & Khodaparast, 2015;Khan et al, 2013). In biological methods, microorganisms are used as a solitary treatment or in the combination with other physical methods and/or chemical technologies (Singhal & Thakur, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary treatment technologies, such as primary clarification and biological treatment, are widely employed for papermaking wastewater treatment (Buyukkamaci and Koken 2010;Svensson and Berntsson 2014). However, conventional processes are not effective for the degradation of refractory organic pollutants; thus, secondary treated effluents still contain a considerable chemical oxygen demand (COD), toxicity, and color (Grötzner et al 2018;Elnakar and Buchanan 2019). Many studies have shown that effluents from P&P mills seriously damage the environment (Ali and Sreekrishnan 2001;Sridhar et al 2011;Wang et al 2012b;Marques et al 2017;Abedinzadeh et al 2018).…”
Section: Introductionmentioning
confidence: 99%